Rethinking normal : a memoir in transition - Hill, Katie Rain; Schrag, Ariel (Simon & Schuster BFYR, 2014)
"In this young adult memoir, a transgender girl shares her personal journey of growing up as a boy and then undergoing gender reassignment during her teens"--